Peer support in small group EFL writing tasks - Guerra Lyons, Jesús David (Universidad Pedagógica y Tecnológica de Colombia, 2016)
This paper reports on a classroom-based research study focused on the issue of support in the context of small group writing tasks in an EFL course. The main interest was in analyzing how learners structure different forms of assistance depending on their intersubjective awareness of each other’s goals and needs in the task. This structuring of learner support was compared to that of teacher-provided support in order to identify similarities and contrasts. Learners were found to provide at least three types of support: cognitive, strategic and feedback support. In each of these support types, specific intersubjective dynamics are reported to unfold as learners’ construed peers’ ongoing needs and goals. Teacher support was found to be mostly strategic, that is, mostly oriented towards task performance. Besides, it is suggested that teacher support often mismatches learners’ needs due to lack of spaces for establishing intersubjective ground. Pedagogical and research implications are finally discussed.